Avaliação clínico-evolutiva dos pacientes pós-primeiro acidente vascular cerebral e o impacto familiar - Cordova, Rosemeire Aparecida Milhim (2007)
Currently, stroke is one of the main death causes and impairments with serious consequences for the patient, relatives and society. The difficulties which come across the caregivers addressed this study that had as objectives: to evaluate the functional independence, the clinical event and the dynamics with the family of patients who suffered the first stroke. This is a descriptive research, cross sectional cohort type, with semi-structure interviews to these caregivers, performed either at hospitals and homes of the city of São José do Rio Preto, Barthel Index ≤40 was used as inclusion criterion, independent of sex or race. The sample comprised 22 patients: 45.45% females and 54.55% males; 22 caregivers, out of these 81.82% were females. The main clinical events presented by the patients were pneumonia 40.91%, pressure ulcers 40.91% and urinary tract infection 36.36%. Out of these 22 patients, 45.45¨% died, of whom 27.27% during the 30 days after the first stroke. The care to the patients is directly related to their impairments; the more unable, more dependent they will be of their caregivers. The dynamics with the relatives are related with the physical effort; the adaptations that have to be provided at home, the fear in working with this patient and the financial needs to support him/her. This study emphasized the importance of the nursing orientations during the hospitalization as well as these patients´ follow-up at home to continue all the care.